Video Conference as a tool for Higher Education the TEMPUS ViCES experience - Caporali, Enrica; Trajkovik, Vladimir (Proceedings e report, 2012)
The book describes the activities of the consortium member institutions in the framework of the TEMPUS IV Joint Project ViCES - Video Conferencing Educational Services (144650-TEMPUS-2008-IT-JPGR). In order to provide the basis for the development of a distance learning environment based on video conferencing systems and develop a blended learning courses methodology, the TEMPUS Project VICES (2009-2012) was launched in 2009. This publication collects the conclusion of the project and it reports the main outcomes together with the approach followed by the different partners towards the achievement of the project's goal. The book includes several contributions focussed on specific topics related to videoconferencing services, namely how to enable such services in educational contexts so that, the installation and deployment of videoconferencing systems could be conceived an integral part of virtual open campuses.